Penguatan Branding Wisata Bukit Pinteir Sebagai Destinasi Wisata Alam, Olahraga, dan Edukasi - Yusuf; Unggul Utan Sufandi; Dessy Mayasari; Hasmonel (Universitas Bangka Belitung, 2026)
The development of tourism destinations based on local potential requires effective branding strategies supported by adequate infrastructure. Bukit Pinteir in Bangka Belitung holds strong potential as a nature-based destination that can be further developed into sports and educational tourism, although it remains constrained by limited supporting facilities. This community service program aims to strengthen destination branding through an applied and participatory approach focused on developing physical infrastructure. The methods include needs assessment, facility design, and implementation through trail improvement, attraction development, information provision, and digital promotion. The results indicate improvements in facility quality, visual appeal, and tourism experience aligned with the nature–sport–education concept. Furthermore, stakeholder involvement enhances local capacity and management skills. This program not only produces functional infrastructure but also fosters sustainable destination branding through community empowerment.